THE INFLUENCE OF BRAND IMAGE AND WORD OF MOUTH ON PURCHASE INTENTION ON SERVICES OF PT. PROTOZA KREASI NUSANTARA JAKARTA - Wardi Saputra; Nurminingsih; Dinni Agustin (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine: 1) Test and explain the influence of Brand Image on Purchase Intention at PT. Pratoza Kreasi Nusantara. 2) Testing and explaining the influence of Word of Mouth on Purchase Intention at PT. Pratoza Kreasi Nusantara. 3. Testing and explaining the influence of Brand Image on the Word of Mouth at PT. Pratoza Kreasi Nusantara 4) Testing and explaining the influence of Brand Image and Word of Mouth on Purchase Intention at PT. Pratoza Kreasi Nusantara. Data were collected through a questionnaire. Data analysis techniques are carried out by organizing and sorting data into patterns, categories, and basic description units so as to answer the research objectives. From the results of this study, it can be concluded that Brand Image is very important as a consumer basis for the Word of Mouth promo. The better the management of Brand Image, the higher the Word of Mouth, and vice versa, the lower the management of the Brand Image, the lower the Word of Mouth. The results of data analysis indicate that Word of Mouth has a positive and significant direct influence on Purchase Intention with a value of 6.58. Likewise, Brand Image and Word of Mouth have a positive and significant indirect influence on Purchase Intention with a value of 6.60> 1.96, as indicated from the coefficient of determination r square. Additionally, the influence of brand image and word of mouth on purchase intention has a value of 6.60%, while the remaining 3.40% is influenced by other factors.